INFLUENCE OF GAS TURBINE ENGINE GAS-AIR CHANNEL OPERATIONAL FACTORS AND DAMAGEABILITY ON ITS COMPONENTS PERFORMANCES - Panin, V.V.; Voznyuk, A.P.; Popov, A.V.; Gaoyong, Sun (Proceedings of National Aviation University (archive), 2005)
This paper deals with the gas-air channel geometry modification, during service life, and its influence on gas turbine engines components performance. Functional relations between gas turbine engine components parameters and run hours are presented.